Computation of end-winding inductance of reluctance machines / Anuar Ibrahim - Ibrahim, Anuar (2010)
The inductance of an electrical machine is hard to be calculated. Nowadays, advancement in finite-element analysis and computer hardware has allowed the calculation of the end-winding inductance of electrical machines or Switched-Reluctance Motor (SRM) more easily. Therefore, this paper introduces a computation of end-winding leakage inductance of electrical machines due to the effect in the end winding itself by using Finite Element Method Magnetics. It is based on a 2D geometric model of the end winding region. The main objective of this paper is to obtain the general empirical curves or equations by means of finite element analysis with the FEMM software.